Efforts to Improve Learning Outcomes of Balance Movements Through Activity-Based Learning in 3rd Grade Students at State Elementary School 1 Landasan Ulin Selatan - Kamaruddin, Kamaruddin; Fauzan , Lazuardy Akbar; Suadmaji, Suadmaji (Empiricism Journal, 2026)
The low balance movement learning outcomes of Grade 3 students at SDN 1 Landasan Ulin Selatan served as the primary urgency of this study, where pre-cycle mastery reached only 39.1% meaning only 9 of 23 students met the individual mastery criterion (score ≥ 75) far below the 80% classical success indicator set for this classroom action research. This study aimed to improve static and dynamic balance movement learning outcomes through the implementation of Activity-Based Learning (ABL). This research employed a Classroom Action Research (CAR) design conducted in two cycles. The research subjects were 23 Grade 3 students at SDN 1 Landasan Ulin Selatan for the 2025/2026 academic year. Data were collected through structured observation using teacher and student activity observation sheets (content-validated by a supervising lecturer) and performance tests using static and dynamic balance assessment rubrics; two raters achieved 92% agreement prior to implementation. Data analysis used comparative descriptive techniques by comparing mastery percentages across cycles. The results demonstrated significant improvement: class average increased from 66.6 (pre-cycle) to 76.0 (Cycle I) and 82.2 (Cycle II). Mastery percentage rose from 39.1% to 60.9% in Cycle I and 91.3% in Cycle II, exceeding the 80% success indicator. Teacher activity improved from 73.9% (Sufficient) to 94.6% (Very Good). It is concluded that the implementation of Activity-Based Learning improved students’ balance movement learning outcomes in this classroom action research context.